La Celestina’s Stage Trajectory in Castilla-La Mancha’s Theather Billboard during the 20th and 21st Centuries - Iván Gómez Caballero (Celestinesca, 2021)
This article analyzes La Celestina's scenic trajectory in Castilla-La Mancha’s theather billboards during the 20th and 21st centuries based on the news found in regional, provincial and local newspapers, as well as graphic materials such as brochures for local festivals. Likewise, it is settled in the work in which towns it has been on stage more often and with which companies, also studying the representations' chronological evolution. Finally, the celestinesque theater billboard of this period is reconstructed in a final annex.